Novel aqueous chitosan-based dispersions as efficient drug delivery systems for topical use. Rheological, textural and release studies. (20th October 2016) - Lucero, M.J.; Ferris, C.; Sánchez-Gutiérrez, C.A.; Jiménez-Castellanos, M.R.; de-Paz, M.-V.
Highlights: A novel thiolated chitosan (CTS) useful as topical drug delivery systems is studied. Theophylline (Th) and Diltiazem (Dt) were chosen as chemically diverse model drugs. Aqueous dispersions were prepared with 1% or 3% w/v CTS and 0.5% w/v drug. All flow curves fit the Herschel-Bulkley model with negative yields stress values. Concentration of CTS and chemical nature of drugs are key factors in drug release. Abstract: The use of a novel cross-linked thiolated chitosan (CTS) was investigated as the main component of aqueous dispersions (at 1% and 3% w/v) for topical drug delivery systems. The nonionic theophiline (Th) and the cationic diltiazem . HCl (Dt) (at 0.5% w/v concentration) were used as model drugs. All aqueous dispersions behaved as viscoelastic fluids. The CTS 1% dispersions showed predominance of viscous component and low viscosity. However, in the CTS 3% dispersions, both the elastic component and high viscosities prevailed. So, texture parameters improved from CTS 1% to 3% dispersions and CTS 3%-Dt showed greater cohesion and adhesion than CTS 3%-Th, but always below CTS alone. All dispersions showed a Fickian diffusion mechanism. Despite release profiles of both drugs almost fully overlapped at 1% CTS, diffusion coefficients confirmed Dt released faster than Th at 3% CTS. The rheological behavior and the chemical nature of the drugs explained these results.